Nature and extent of human-elephant conflict in Bia Conservation Area, Ghana - Sam, Kofi; Emmanuel Danquah; Samuel Oppong; Enoch Ashie (Pachyderm)
During the 2004 rainy season the nature and extent of human-elephant conflict focused on crop raiding and damage was investigated in and around Bia Conservation Area (comprised of two forest areas Bia NP and Bia Resource Reserve to the south of the Park). 49 elephant crop raiding incidents involving 44 farms belonging to 36 farmers from 18 villages were recorded during the study period. Questionnaire based interviews were undertaken with 42 randomly selected members of 11 randomly selected fringe communities of the 20 major communities witin 7 kms of the Conservation Area boundary. Information on the current crop damage was collected within 48 hours of the incident: field location, size, crop type and growth stage, extent of damage were recorded. Severe crop damage starts in June and increases until peaking in September/October and then declines until becoming minimal in December. The majority of interviewees (72%) were new immigants to the area, and had no idea about the relative number of elephants in the area. Over 90% employed some kind of traditional deterrent for driving the elephants away. Based on visual and track identification it appeared that at least 24 male and 12 female elephant were involved in the raiding incidents. In term of age 43 adults and 33 subadults and infants were seen on different occasions. Elephant crop raiding dates to the 1970s when immigrants came to the area and began farming in close proximity to the reserves. It has increased, now family groups as well as bulls raid, raiding occurs anytime of the day and throughout the year, although it is most prevalent in the wet season here as it is in Kakum CA. Farmers should be encouraged to protect their crops. However, elephants habituate to many scare techniques, farmers must constantly assess the risk involved including planting fields far from areas frequented by migrating elephant.